2021
DOI: 10.1111/dme.14625
|View full text |Cite
|
Sign up to set email alerts
|

Same goals, different challenges: A systematic review of perspectives of people with diabetes and healthcare professionals on Type 2 diabetes care

Abstract: Aims To identify the views of people with Type 2 diabetes (PWD) and healthcare professionals (HCP) about diabetes care. Methods A systematic review of qualitative studies reporting both groups’ views using thematic synthesis frameworked by the eHealth Enhanced Chronic Care Model was conducted. Results We searched six electronic databases between 2010 and 2020, identified 6999 studies and included 21. Thirty themes were identified with in general complementary views between PWD and HCP. PWD and HCP find lifesty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
(242 reference statements)
0
15
0
Order By: Relevance
“…Similarly to these findings, a systematic review conducted by our team concluded that generally both groups have similar views about components of diabetes care, but HCPs struggle to meet PWD's holistic needs. 17 This demonstrates that there is an alignment of the perceived needs for improved diabetes care among main stakeholders, however, important gaps still remain. Other studies have identified gaps between what stakeholders wish for and what healthcare systems deliver.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly to these findings, a systematic review conducted by our team concluded that generally both groups have similar views about components of diabetes care, but HCPs struggle to meet PWD's holistic needs. 17 This demonstrates that there is an alignment of the perceived needs for improved diabetes care among main stakeholders, however, important gaps still remain. Other studies have identified gaps between what stakeholders wish for and what healthcare systems deliver.…”
Section: Discussionmentioning
confidence: 98%
“…All steps were guided by key stakeholders' contributions, and information uncovered at each step influenced the next until a solution was designed and endorsed by all. Step 1 included a literature review, published separately as a systematic review, 17 and review of grey literature. This article reports the subsequent part of step 1—focus groups and interviews with stakeholders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing patients with knowledge about diabetes and self-care behaviors could increase awareness of the necessity of self-management, which motivated self-management engagement in route life [19][20][21][22][23][24][25][26][27][28][29]. However, people with diabetes could be reluctant to obtain new knowledge about diabetes and to use the knowledge to manage diabetes in routine life [20,[25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, people with diabetes could be reluctant to obtain new knowledge about diabetes and to use the knowledge to manage diabetes in routine life [20,[25][26]. This might be caused by that the knowledge was inconsistent with personal demands and was not culturally sensitive [19][20][21][22][23][24][25][26][28][29] Social support could increase self-management engagement [19][20][21][22][23][24][25][27][28][29]. However, the in uences of social support on diabetes self-management engagement were various across populations of different continents [19][20][21][22][23][24][27][28][29].…”
Section: Introductionmentioning
confidence: 99%